Tentukan hp dengan cara substitusi 1. 2×-3y=6 ×-y=1

Posted on

Tentukan hp dengan cara substitusi
1. 2×-3y=6
×-y=1

2x – 3y = 6 ………(1)

x – y = 1 | x2

2x – 2y = 2 …….. (2)

Masukkan persamaan (2) ke persamaan (1)

2x – 3y = 6

2 – y = 6

y = -4 ……. (3)

Masukkan persamaan (3) ke (1)

2x – 3y = 6

2x – 3(-4) = 6

2x + 12 = 6

2x = -6

x = -3

Semoga membantu

Jawaban:

2x – 3y = 6

x – y = 1

____________

=> 2x – 3y = 6 | x 1

x – y = 1 | x 3

=> 2x – 3y = 6

3x – 3y = 3

____________ –

– x = 3

x = -3

=> x – y = 1

-3 – y = 1

– y = 1 + 3

y = -4